Digital visual communication and perception of corporate identity in Higher Education Institutions - Holguín Martínez, Katherine; Peñafiel Guiracocha, Viviana; Galarza Lucio, Jair (Scripta Mundi, 2024)
This article analyzes the digital visual communication of some Higher Education Institutions in the city of Guayaquil from a corporate identity scope and the perception that design professionals have of those institutions; for which it was intended to examine some of the main public and private Universities of Guayaquil, Ecuador, mainly implementing a visual analysis in order to establish the most notable differences between the identity management of public and private universities in Ecuador, so that it is possible to identify and know the main communicational characteristics of each institution and the influence that communication has on those institutions according to professionals in design and communication. The approach of this research is qualitative, descriptive, and analyzes the graphic brand of eight universities, four public and four private; shape, color, typography and verbal message. Among the main conclusions it could be observed that private universities similarly project digital visual communication, with the use of simple and concrete logotypes that convey messages that denote strength, seriousness and trajectory using Isologos type logotypes, composed of an icon and logo, which adds a marked style among private institutions. In the case of public universities, more variety could be identified and therefore noticeable differences among the same group.